Der Weg der Roten Fahne. Art in correlation to architecture, urban planning and policy - Fülscher, Christiane (Journal of Architecture and Urbanism, 2013)
The presented research focuses on the relationship between art and architecture. On the example of the mural Der Weg der Roten Fahne (The Path of the Red Flag) installed at the western façade of the Kulturpalast Dresden(Palace of Culture in Dresden) the author analyses the necessity of the mural as an immanent element to communicate political decisions of the German Democratic Republic’s government to the public by using architecture. Up until now the mural reinforces the political value of the International Style building in function and shape and links its volume to the urban layout.